Cyclic peptide therapeutics: past, present and future. (June 2017) - Zorzi, Alessandro; Deyle, Kaycie; Heinis, Christian
Highlights: On average, one cyclic peptide drug is approved every year. New strategies based on rational design and in vitro evolution deliver peptides to new targets. Many of the more than 20 cyclic peptides in clinical trials were developed de novo . Oral availability and cell permeability remain challenges to peptide therapeutics. Abstract : Cyclic peptides combine several favorable properties such as good binding affinity, target selectivity and low toxicity that make them an attractive modality for the development of therapeutics. Over 40 cyclic peptide drugs are currently in clinical use and around one new cyclic peptide drug enters the market every year on average. The vast majority of clinically approved cyclic peptides are derived from natural products, such as antimicrobials or human peptide hormones. New powerful techniques based on rational design and in vitro evolution have enabled the de novo development of cyclic peptide ligands to targets for which nature does not offer solutions. A look at the cyclic peptides currently under clinical evaluation shows that several have been developed using such techniques. This new source for cyclic peptide ligands introduces a freshness to the field, and it is likely that de novo developed cyclic peptides will be in clinical use in the near future.